D ?S-Closed Sets in Topological Spaces - S.Sumithra Devi, L.Meenakshi Sundaram (Mathematical Statistician and Engineering Applications, 2023)
In this paper, we introduce a new classes of sets called S-Closed Sets in Topological spaces and study some basic properties of S-Closed Sets.